Основы методической деятельности учителя в процессе обучения младших школьников математике - Кочеткова, И.А. (Wielkopolska Rada Młodzieży, 2012)
Autorka w swoim artykule porusza zagadnienia dotyczące metodycznych założeń działalności nauczyciela w procesie nauczania matematyki w młodszych klasach szkolnych (przedszkolnych).

The author focuses on issues concerning methodological assumptions of teacher's work in the process of teachning preschool and young children matchematics.
Keywords: proces nauczania; matematyka